Bimetallic copper/cobalt-cocatalyzed double aerobic phenol oxidation/cyclization toward π-extended benzofuro[2, 3-b]indoles as electron donors for electroluminescence. Issue 14 (29th June 2021) - Bashir, Muhammad Adnan; Zhang, Yulong; Yu, Huaibin; Wang, Bofei; Zhao, Weining; Zhong, Fangrui
Abstract : π-Extended benzofuro[2, 3- b ]indoles were efficiently constructed from readily available p -hydroquinone esters and indoles via aerobic oxidation. Abstract : Benzofuro[2, 3- b ]indoles, apart from their attractive biological features, constitute a novel family of electron donors for electroluminescent materials. Reported herein is the establishment of a strategy involving bimetallic catalysis to form such π-conjugated extended frameworks, specifically via the CoCl2 /Cu(OTf)2 -catalyzed double aerobic oxidative cycloaddition of indoles with p -hydroquinone ester. The crucial and distinct roles of the two metals salts and the alcohol solvent were clarified. This oxidation system enabled the disruption of the well-established acid-catalyzed quinone–indole [3 + 2] cycloaddition reaction favoring benzofuro[2, 3- b ]indolines and is superior to previously known multi-step synthetic methods involving Pd-catalyzed cross-coupling with pre-functionalized (pseudo)halides. Moreover, the photophysical properties of the product were preliminarily investigated, the results of which suggested the potential of these polycyclic heteroaromatics to be used in efficient deep-blue organic light-emitting diodes.